2007
DOI: 10.1111/j.1365-2265.2007.02852.x
|View full text |Cite
|
Sign up to set email alerts
|

l‐selectin gene polymorphisms in Graves' disease

Abstract: L-selectin gene polymorphisms are associated with GD susceptibility in Chinese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…In the current study, the frequencies of the 213 S (725T) alleles among the healthy controls was 0.334, and this was similar to those frequencies observed in Wuhan and Shanghai of Chinese healthy Han race (0.307 and 0.370, respectively) [8,12], but the frequencies were higher than those of European populations (0.139 and 0.160, respectively) [13,14]. Suggesting that the distribution of L-selectin gene frequencies might vary among the different ethnic groups.…”
Section: Discussionsupporting
confidence: 88%
“…In the current study, the frequencies of the 213 S (725T) alleles among the healthy controls was 0.334, and this was similar to those frequencies observed in Wuhan and Shanghai of Chinese healthy Han race (0.307 and 0.370, respectively) [8,12], but the frequencies were higher than those of European populations (0.139 and 0.160, respectively) [13,14]. Suggesting that the distribution of L-selectin gene frequencies might vary among the different ethnic groups.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, SELE and SELL within the selectin gene cluster seem to be prone to contribute susceptibility to a single autoimmune disease together, as shown in the findings in IgA nephropathy 25 and coeliac disease. 26 In the light of the evidence in the association of SELL with GD, 9 the association of SELE with GD could be a reasonable deduction.…”
Section: Resultsmentioning
confidence: 99%
“…23,24 Recently, we identified the association of GD and specific SNPs within SELL by means of a case-control study. 9 In addition, the common variants in selectin gene cluster on chromosome 1q24-25, including SELE and SELL, are in nearly complete linkage disequilibrium (data from www.hapmap.org). The two selectin genes might therefore contribute to the susceptibility to GD through either a mutual interaction or a common pathway, though we did not observe any direct evidence in this study.…”
Section: Resultsmentioning
confidence: 99%
“…[112, 113]. Chen H, et al [114, 115] reported common L-selectin or E-selectin variants may be associated with susceptibility to Graves’ disease in Chinese population. Cytokines, a large group of non-enzymatic proteins, participate in the induction and effector phases of all inflammatory and immune responses, and are therefore likely to play a critical role in the development of autoimmune diseases [116].…”
Section: Hyperthyroidismmentioning
confidence: 99%